Effect of spacing on P and Zn uptake of local T. Aman rice varieties in Khulna area - Parvin, S; Islam, MM; Mondal, MK; Quddus, KG; Mahmud, AM (Bangladesh Agronomy Journal, 2015)
A field experiment was conducted at the Agronomy field of Khulna University, Khulna during T. Aman season to evaluate the effects of spacing on nutrient content and total uptake of phosphorus and zinc by grain and straw of traditional rice of Khulna region. The experiment was laid out in split-plot design with three replications assigning three varieties viz., Jotai, Bashfulbalam, Ranisalute and three spacings viz., 30 cm x 30 cm, 40 cm x 40 cm and 50 cm x 50 cm. The variety was assigned in main plot and spacing in sub plot. The plot was fertilized with 40-50-35-5 kg of Urea-TSP-MOP and ZnS04 ha-1 respectively. The results indicated that the single effect of variety and spacing on P and Zn content in grain and straw varied significantly while the straw P content was found insignificant. The interaction effect of variety and spacing on P and Zn content was found significant in all the treatments. The highest P and Zn content of grain was found from the variety Ranisalute at 50 cm x 50 cm (V3S1) but in straw from Ranisalute x 40 cm×40 cm (V3S2) and Bashfulbalam x 30 cm × 30cm (V2S1), respectively. The total uptake of P and Zn was found the highest from Jotai variety at 30 cm x 30 cm spacing. From the interaction it showed that the highest P and Zn uptake was found from Jotai x 30 cm × 30 cm (V1S1) and the lowest from Ranisalute x 50 cm x 50 cm (V3S3). The study indicated that though wider spacings of 40 cm x 40 cm and 50 cm x 50 cm increased the number of tillers hill-1 and nutrient uptake but it cannot increase the nutrient uptake and grain yield ha-1. So, 30 cm x 30 cm spacing showed positive relationship on nutrient uptake than 40 cm x 40 cm and 50 cm x 50 cm spacing. Bangladesh Agron. J. 2014, 17(1): 81-88